Quantitative determination of major nandrolone metabolite in human urine by gas chromatography/mass spectrometry - Shahoika, Pavel G.; Ahabalayeu, Aliaksandr A.; Tchekhovskaya, Olga N.; Pakhadnia, Yury G.; Beliaev, Sergey A.; Leschev, Sergey M. (Journal of the Belarusian State University. Chemistry, 2019)
Nandrolone is an anabolic androgenic steroid. The use of this substance is prohibited by World Anti-Doping Agency (WADA). In National Anti-Doping Laboratory, we have developed method for quantitative determination of major nandrolone metabolite – 19-norandrosterone in human urine by GC/MS technique (Agilent 7000). Proposed method includes sample preparation of urine samples with enzymatic hydrolysis, liquid-liquid extraction followed by derivatization step with MSTFA. Deuterated 19-norandrosterone has been used as internal standard. Total run time comprised 16 min. Lower limit of quantitation accounted for 1 ng/mL. Spiked urine samples were prepared by mixing blank urine with standard solutions of 19-norandrosterone in range 1–30 ng/mL, correlation coefficient larger than 0.99. Method was verified tofollowing validation parameters: selectivity, linearity, repeatability, accuracy, matrix effect, stability and robustness. Furthermore, measurement uncertainty was estimated. Thus, proposed method is able to detect threshold 19-norandrosterone in human urine and carry out its quantitation conforming WADA requirements.
Keywords: 19-norandrosterone; nandrolone; gas chromatography; mass spectrometry; doping-control; androgenic anabolic steroid; quantitative determination